The combined effect of dietary live microbe intake and physical activity on overweight or obesity in children and adolescents aged 2–17 years: a cross-sectional study from the NHANES - Wang, Shanhu; Chen, Xiaoli; Wu, Yangyang (Frontiers in Pediatrics, 2025)
AimThe study aimed to explore the combined effect of dietary live microbe intake and physical activity on overweight or obesity in children and adolescents aged 2–17.MethodsData of children and adolescents aged 2–17 were obtained from the National Health and Nutrition Examination Surveys (NHANES) database in 1999–2020. Dietary live microbe intake was assessed through 24-h dietary recalls and categorized into three levels: low, medium, and high (with “MedHi” referring to the combined medium and high intake groups for analysis). Physical activity level was determined by self-reported using the questionnaire. Overweight and obesity was evaluated using the body mass index-for-age percentile growth charts. Weighted univariate and multivariate logistic models were conducted to explore the associations between dietary live microbe intake, physical activity, and overweight or obesity in children and adolescents. With odds ratios (ORs) and 95% confidence intervals (CIs) presented.ResultsAmong the included children and adolescents, 10,086 had overweight or obesity. We found that those with high live microbe intake (from the MedHi group) and ideal physical activity had the lowest incidence of overweight or obesity (χ2 = 52.311, P < 0.001). Specifically, children and adolescent with high live microbe intake and ideal physical activity were related to a lower occurrence of overweight or obesity (OR = 0.65, 95%CI: 0.54–0.77). The expression levels of enterodiol and enterolactone were the highest in the high live microbe intake and ideal physical activity group. CRP expression levels were lowest in high live microbe intake and ideal PA group.ConclusionDietary live microbe intake and physical activity has a potential combined effect on overweight or obesity in children and adolescents. Further longitudinal studies are needed to confirm the causal relationships and explore the mechanisms.